Identity Construction and Classroom Participation Of An Indonesian Graduate Student In An Australian University - M. Faruq Ubaidillah; Utami Widiati (Lembaga Penelitian dan Pengabdian Masyarakat IAIN Kediri, 2021)
This narrative study explores identity construction and classroom participation of an Indonesian student who attended a master program in TESOL in an Australian university. Grounded from identity and investment frameworks (Norton, 2000) and situated learning theory (Lave & Wenger, 1991), the study specifically probes into the changing identity construction across time shaped by the participant’s involvement in the community of practice. Data analysis followed Polkinghorne’s (1995) categorical procedure and Connelly and Clandinin’s (2006) three-dimensional space of narrative inquiry. The findings portray gradual and complex identity construction mediated by the participant’s agentive classroom participation. It was also found that the participant’s identity evolved across time together with a movement from peripheral to full participation. This study informs that L2 learning is dependent on social, emotional, cultural, and situated practices depicted in L2 learner’s classroom participation. It also highlights the need for incorporating narrative inquiry to understand multiple, subjective, and conflicting values in L2 learning and other educational contexts.